Substitution Phalloplasty in Patients with Bladder Exstrophy-Epispadias Complex: A Systematic Review of Techniques, Complications and Outcomes. Issue 2 (19th November 2020) - Berrettini, Alfredo; Sampogna, Gianluca; Gnech, Michele; Montanari, Emanuele; Manzoni, Gianantonio; Di Grazia, Massimo; Castagnetti, Marco
ABSTRACT: Background: Males born with bladder exstrophy-epispadias complex generally have a shorter phallus, split corpora with dorsal curvature, and a scarred and flattened glans, so substitution phalloplasty is often required. Aim: The aim of this study was to review the techniques, complications, and outcomes of substitution phalloplasty in bladder exstrophy-epispadias complex patients to determine the ideal surgical procedure and gauge the risks and benefits for the patient. Methods: A systematic review of the literature was performed using PubMed/MEDLINE and the Cochrane Library with the following terms: ("phalloplasty"); (("epispadias") OR ("bladder exstrophy") OR ("cloacal exstrophy")). We included only full-text articles reporting data about techniques and outcomes of substitution phalloplasty in patients with bladder exstrophy-epispadias complex. Outcomes: To determine whether patients with bladder exstrophy-epispadias complex might benefit from substitution phalloplasty. RESULTS: We selected 7 studies involving 47 patients. All the studies were characterized by a low level of evidence and a heterogeneous approach during treatment and outcome assessment. The free radial forearm flap was the most commonly performed technique (89%) with an overall complication rate of 15%. Urethroplasty was performed in 22 of 47 (47%) patients, and in most cases (20/22) a "tube-within-the-tube" technique was performed simultaneously with the phalloplasty (20/47). Urethroplasty complications were recorded in 12 of 22 (54%) patients with 6 fistulae and 6 stenoses. A penile prosthesis was implanted in 32 of 47 (68%) patients and complications occurred in 8 of 32 (25%) patients with 6 erosion. Aesthetic, sexual, and psychological outcomes were satisfactory, but none of the studies used validated instruments for the final assessment. Clinical Implications: It was not possible to formulate any recommendations based on a high level of evidence regarding substitution phalloplasty in patients with bladder exstrophy-epispadias complex. Strength & Limitation: To our knowledge, this is the first review to address bladder exstrophy-epispadias complex patients only. The limitations are mainly represented by the small number of cases because of the rarity of this disease and by the fact that no studies used validated instruments. CONCLUSION: Substitution phalloplasty in patients with bladder exstrophy-epispadias complex can achieve good functional, aesthetic, psychological, and sexual outcomes. It requires multiple procedures and carries a high complication rate. Multicentric studies including the assessment of patients by means of a validated questionnaire which investigates both sexual function and psychosexual satisfaction are required.